072. Subhepatic Appendicitis in A 23 Year Old Woman: A Rare Case Report - Kartinasari, Apidha; Fauzie, Rayhan (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical Education, 2024)
Background : Subhepatic appendicitis is a rare condition that occurs in only 0.01% of all acute appendicitis cases. The subhepatic position of the appendix is due to a developmental anomaly resulting from the failure of the caecum to descend during embryonic development. Its symptoms often resemble those of other diseases such as cholecystitis, pyelonephritis, and urolithiasis, which can lead to a delay in diagnosis and treatment. Case :  A 23-year-old woman presented with four-day history of pain in the right upper quadrant of her abdomen, fever, anorexia, nausea, and vomiting. Abdominal examination revealed tenderness of all abdominal quadrants, which was more pronounced over the right upper and middle quadrant with positive rebound tenderness.  Laboratory tests showed high levels of neutrophilic leukocytosis. Ultrasound imaging revealed an inflamed vermiform appendix in the subhepatic region. A diagnosis of an abnormally located appendix was made, and the patient underwent laparotomy. During exploration, an inflamed appendix was found covered by omentum in the right upper quadrant, and appendectomy was carried out smoothly. The patient was in good clinical condition without any complications. Conclusion: Subhepatic appendicitis presents a significant challenge to clinicians due to its unusual location. Failure to diagnose and manage it promptly can lead to complications such as abscesses, peritonitis, sepsis, and increased morbidity. Midline laparotomy is recommended due to the subhepatic location of the appendix and the possibility of retrocecal, dense adhesion or fibrosis, and perforation, which would make a laparoscopic approach unsafe.